Characterisation of dislocation behaviour in RPV steel - Monnet, G.; Domain, C.; Bacon, D.; Terentyev, D. (Вопросы атомной науки и техники, 2009)
Results obtained in the framework of the European project PERFECT (FI60-CT-2003- 208840) are presented.